IGFBP1 inhibits the invasion, migration, and apoptosis of HTR-8/SVneo trophoblast cells in preeclampsia - Xiujuan Li; Chenxi Li; Ye Wang; Jianxing Cai; Li Zhao; Zhiying Su; Huiming Ye (Taylor & Francis Group, 2022)
Objective To investigate the effects and underlying mechanisms of IGFBP1 on the biological functions of trophoblasts in simulated preeclampsia. Methods IGFBP1 expression in placenta was determined by immunohistochemistry. HTR-8/SVneo cells were stimulated with/without IGFBP1-overexpression and hypoxia-reoxygenation, and the proliferation, invasion, migration, and apoptosis were detected by CCK8, transwell, and flow cytometry, respectively. Results IGFBP1 expression was increased in placenta of preeclampsia. IGFBP1 overexpression inhibited proliferation, invasion, migration, and apoptosis of HTR-8/SVneo cells and induced MMP-26 expression with/without hypoxia-reoxygenation challenge. Conclusion IGFBP1 affects biological functions of trophoblasts, and it may play a role in pathophysiology of preeclampsia by inducing MMP-26.